Speed sensorless control of a bearingless induction motor based on sliding mode observer and phase-locked loop. (April 2022) - Yang, Zebin; Ding, Qifeng; Sun, Xiaodong; Lu, Chengling; Zhu, Huimin
Abstract: To realize the low-cost and high-performance of a bearingless induction motor (BIM), a speed sensorless control strategy combined with the improved sliding mode observer (SMO) and phase locked-loop (PLL) is proposed. Based on analyzing the principle of the traditional SMO, the improved SMO adopts a switching function that has a double boundary layer structure to reduce the high-frequency jitter. Firstly, the observation equation of the rotor flux is established where the stator current, as well as the rotor flux are two state variables, and then the system stability is discussed with the Lyapunov theory. Secondly, to reduce the rotor chatter and enhance the speed tracking performance a flux electrical angle detecting module is constructed based on the PLL structure that extracts the rotor flux electrical angle and speed from the observed flux component. Finally, the BIM speed sensorless vector control system is established and the simulation results and experimental results are respectively presented by the MATLAB/Simulink simulation platform and a laboratory prototype. Both results prove that this strategy can not only enhance the speed self-detection capability and tracking performance, but can guarantee the excellent self-suspension function as well. Highlights: The SMO of the new type induction motor BIM is designed. The switching function with double boundary layer is introduced into the SMO. The rotor flux electrical angle detecting module is constructed based on the PLL.